2018
DOI: 10.3389/fphar.2018.00920
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mitochondrial Oxidative Stress to Mitigate UV-Induced Skin Damage

Abstract: Unmitigated UV radiation (UVR) induces skin photoaging and multiple forms of cutaneous carcinoma by complex pathways that include those mediated by UV-induced reactive oxygen species (ROS). Upon UVR exposure, a cascade of events is induced that overwhelms the skin’s natural antioxidant defenses and results in DNA damage, intracellular lipid and protein peroxidation, and the dysregulation of pathways that modulate inflammatory and apoptotic responses. To this end, natural products with potent antioxidant proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 98 publications
0
67
0
1
Order By: Relevance
“…Protection of outdoor workers exposed to SR should ideally include the shielding of IRA, which is now difficult to achieve optimally. Solar IRA represents a reason, besides others, to continue to explore in depth the role of topical and systemic antioxidants, including those active in mithocondria [112].…”
Section: Discussionmentioning
confidence: 99%
“…Protection of outdoor workers exposed to SR should ideally include the shielding of IRA, which is now difficult to achieve optimally. Solar IRA represents a reason, besides others, to continue to explore in depth the role of topical and systemic antioxidants, including those active in mithocondria [112].…”
Section: Discussionmentioning
confidence: 99%
“…As a control for our probiotic mitigators, the GS-nitroxide, JP4-039 (1), was prepared and administered according to published methods, i.m. at 20 mg/kg in 50 μl of 30% cyclodextrin aqueous (34). Cyclodextrin alone has no radiomitigative effect (34).…”
Section: Administration Of Small Molecule Radiation Mitigator Il-22mentioning
confidence: 99%
“…Sunlight, especially its ultraviolet (UV) light component, is the major factor that causes skin photoaging, which results in facial hyperpigmentation and wrinkle formation 1 UV light leads to collagen degradation and dysregulation of extracellular matrix homeostasis, and induces extensive skin damage through direct DNA damage, the production of reactive oxygen species (ROS), which cause lipid and protein peroxidation, and immune dysregulation that results in cell dysfunction and death. 2 DNA damage caused directly by UV light and ROS generated by UV exposure may result in defective DNA repair and gene mutations. 3 In vivo and in vitro studies have shown that oxidative stress and DNA damage in the skin caused by UV exposure are alleviated by the intake of antioxidants including vitamins, carotenoids and polyphenols.…”
Section: Introductionmentioning
confidence: 99%